Particles and fragments in unused disposable face masks: A microscopic analysis (International Journal of Occupational Safety and Health, 2022)
Introduction: In the context of the COVID-19 pandemic, many governments mandated the wearing of face masks by law. New research shows that these masks contain and release microplastics.Methods: In the present work, five samples of surgical masks were examined microscopically for the presence of particles and fragments. The masks were purchased from two of the largest supermarket chains in Switzerland.Results: Particles and fragments were found on the fiber surfaces in the inner layer of all face masks examined. The size of these objects varied in the range of about 2-40 µm, with dark spots and particles on the fibers having a smaller diameter than the more transparent fragments.Conclusions: In this work, it was shown that particles and fragments in the micrometer range can be found on the inside of commercially available surgical face masks purchased in supermarkets in Switzerland. The health significance of the presence of particles and fragments in the micrometer range as demonstrated by the current investigation of surgical face masks needs to be further investigated.